ANALISIS PEMBENTUKAN KERJASAMA ANTAR DAERAH: SEBUAH STUDI EFFEKTIVITAS KOORDINASI BAKORWIL BOJONEGORO DALAM INISIASI SEKRETARIAT BERSAMA GREBANG RATUBANGNEGORO KERTOWILANGAN - Memorial, Moch. Bianda Kim; Ma'ruf, Muhammad Farid (Publika, 2024)
Inter-regional cooperation is an effort by two or more regions to achieve common goals in accordance with needs. Bakorwil Bojonegoro initiated the formation of collaboration between eight regencies/cities within its working area, plus three bordering regencies, thus forming the acronym Grebang Ratubangnegoro Kertowilangan. However, in this collaboration there is a problem regarding the length of time for establishing this joint secretariat so that the Grebang Ratubangnegoro Kertowilangan Cooperation has not yet started. This delay means that districts/cities cannot implement cooperation with a legal umbrella. This research aims to find out, describe and analyze Bakorwil Bojonegoro in coordinating the formation of cooperation between the Grebang Ratubangnegoro Kertowilangan regions and its obstacles. This research method uses a qualitative approach with content and discourse analysis techniques. In this research, the instrument was developed from Hasibuan's theory (2011) by sharpening the factors that influence coordination, namely unity of action, communication, division of work, discipline. The research findings produced during the analysis are: (1) there are obstacles in the formation of a joint secretariat where officials at the district/city government level have their own activities, (2) there are differences in signing procedures to the regent/mayor, (3) Change of officials during the secretariat formation meeting together and officials asked for time to review. Judging from these obstacles, the suggestions from the researchers are (1) Each district/city can be more aware of the importance of this collaboration, (2) Every meeting of the Bojonegoro Bakorwil collaboration activity can be more reminded that all activities must be carried out in accordance with the agreement, (3) Bojonegoro Bakorwil can remind the relevant officials more frequently whenever there are activities to form inter-regional cooperation, (4) Every time a regency/city official changes, the old official informs the new official about the Grebang Ratubangnegoro Kertowilangann inter-regional cooperation so that it is implemented more optimally.